Diabetes-related distress and daily cortisol output in people with Type 2 diabetes. (November 2020) - Bawa, Hetashi; Poole, Lydia; Cooke, Debbie; Panagi, Laura; Steptoe, Andrew; Hackett, Ruth A.
Abstract: Aims: Diabetes-related distress is common in Type 2 Diabetes and is linked with poor diabetes control. However, mechanisms underlying this association are unclear. One pathway that could be involved is neuroendocrine dysfunction, as Type 2 Diabetes is associated with altered diurnal cortisol output. This study investigated the link between diabetes-related distress and diurnal cortisol output. Methods: 134 people with Type 2 Diabetes provided 5 cortisol samples over the course of a day. Multivariate linear regression models were used to assess whether overall and sub-domains of diabetes-related distress measured by the Diabetes Distress Scale, predicted cortisol parameters (waking cortisol, cortisol awakening response, cortisol slope and evening cortisol). Results: Physician-related distress was associated with greater waking ( B  = 2.747, p  = .015) and evening cortisol ( B  = 1.375, p  = .014), and a blunted cortisol awakening response ( B  = −3.472, p  = .038) adjusting for age, sex, income, body mass index, smoking and time of awakening. No associations were detected for overall distress, emotional, interpersonal or regimen distress. Conclusion: Physician-related distress was associated with alterations in daily cortisol output. Longitudinal research is required to understand how physician-related distress is associated with diurnal cortisol patterning over time.